Hand-assisted laparoscopic living donor nephrectomy: initial Glasgow experience. Issue 4 (November 2013) - Hanif, F; Clancy, MJ
Aims: The study presents the early results of hand-assisted laparoscopic living donor nephrectomy (HALDN) carried out in West of Scotland from June 2009 to October 2010. Methods: The first 20 HALDN procedures carried out in our unit are presented. The outcomes reported are warm ischaemia time, operative time, delayed graft function, recipient renal function and one-month morbidity and mortality of donor and recipient. SPSS 15.0 was used for statistical analysis. Results: The mean age of the donors was 44 ± 10 years, predominantly females ( n = 13), median operative time 135 ± 33 min and warm ischaemia time 41 ± 16 s. The length of the incision used was 65 mm in all cases. Duration of hospital stay was 5 ± 1 days. Patient mortality was 0 and morbidity minimal with two donors developing minor wound infection and no other clinically significant postoperative morbidity. Among the recipients, 18/20 (90%) transplants worked primarily with two delayed graft functions, one due to early surgical complications in a small paediatric recipient and one due to recipient renal artery thrombosis. Conclusion: HALDN is safe and associated with minimal morbidity; further analysis aims to confirm excellent cosmetic results and quick return to activity compared with the standard open nephrectomy technique.